Hipersuperfícies no espaço hiperbólico associadas à equação da curvatura escalar constante - Machado, Cid Dias Ferraz (2014)
In this work we present a study of a class of oriented hypersurfaces in hyperbolic space satisfying a special linear relation between the rth mean curvatures which is based on a Walterson Ferreira and Pedro Roitman’s article, where this class is characterized by a harmonic map derived from the two hyperbolic Gauss maps.We also show the relation of such hypersufaces with solutions of the equation Du+kun+2 n2 = 0, where k 2 f1;0;1g.